2004
DOI: 10.1002/yea.1108
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium transport in the halophilic yeast Debaryomyces hansenii

Abstract: Debaryomyces hansenii, a halophile yeast found in shallow sea waters and salty food products grows optimally in 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
(37 reference statements)
1
36
0
Order By: Relevance
“…In D. hansenii, even though a lower capacity of the K + transport systems was observed, it was proposed that a higher Na + intracellular content could help cells to overcome the lack of K + when it is scarce (Gonzalez-Hernandez et al, 2004). This cannot be the case for the S. cerevisiae transformant strains, since Na + should still be toxic when accumulated inside these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In D. hansenii, even though a lower capacity of the K + transport systems was observed, it was proposed that a higher Na + intracellular content could help cells to overcome the lack of K + when it is scarce (Gonzalez-Hernandez et al, 2004). This cannot be the case for the S. cerevisiae transformant strains, since Na + should still be toxic when accumulated inside these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, a few authors have described several features of this yeast related to its extreme halotolerance; these studies have focused on glycerol production and accumulation (Larsson et al, 1990;Lages et al, 1999), cation fluxes (Norkrans & Kylin, 1969;Prista et al, 1997;Gonzalez-Hernandez et al, 2004), and pH (Mortensen et al, 2006) and Na + targets (Aggarwal et al, 2005). Some of these studies have considered D. hansenii as a halophilic yeast (Gonzalez-Hernandez et al, 2004) and used this organism as a model for the study of salt tolerance mechanisms in eukaryotic walled cells (Prista et al, 2002(Prista et al, , 2005. The recent release of the complete sequence and annotation of the D. hansenii genome by the Génolevure consortium (Dujon et al, 2004) revealed that most known pathways involved in salt tolerance in S. cerevisiae are also present in D. hansenii (Prista et al, 2005) and also brought new perspectives to molecular studies in this yeast.…”
Section: Introductionmentioning
confidence: 99%
“…D. hansenii is a halotolerant yeast species that has attracted a lot of attention in the last few years. Although it was shown that sodium is not specifically toxic for D. hansenii (Prista et al, 1997) and some authors concluded, based on sodium and potassium transport experiments in D. hansenii, that sodium is not excluded in this yeast but instead its metabolic systems are resistant to high sodium concentrations (Gonzalez-Hernandez et al, 2004), D. hansenii must certainly possess systems for cation exclusion to avoid osmotic stress caused by high salt concentrations. Sodium efflux from D. hansenii is not significantly affected by pH which suggests that Na + /H + antiport is not the main mechanism involved (Almagro et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
“…All these results suggest that D. hansenii could possess alkalimetal-cation transporters with specific properties. Two genes encoding DhEna1 and DhEna2 Na + -ATPases have been isolated and their protein products characterized upon heterologous expression in S. cerevisiae cells (Almagro et al, 2001), and the existence of a non-selective Na + and K + channel was proposed based on cation flux measurements (Gonzalez-Hernandez et al, 2004). For further study of this non-conventional yeast species, the recent sequencing of its complete genome has been very important (Dujon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A few ones, in particular some Halobacteria, require high intracellular concentrations of sodium for normal enzymatic activities (the "sodium includers") [17]. Although mechanisms of sodium extrusion are present in D. hansenii, several authors reported unusual high intracellular salt concentrations in this yeast [8,14]. From this point of view, D. hansenii may be considered as a "sodium includer" yeast, up to some extent: still an important role is reserved for the production and intracellular retention of compatible solutes, glycerol in particular [1,4,9].…”
Section: Debaryomyces Hansenii Among Salt Tolerant Microorganismsmentioning
confidence: 99%